Combination of ultrasound and chlorogenic acid for inactivation of planktonic and biofilm cells of Pseudomonas fluorescens. (May 2022) - Sun, Jinyue; Huang, Lihan; Sun, Zhilan; Wang, Debao; Liu, Fang; Du, Lihui; Wang, Daoying
Graphical abstract: Highlights: Treatments of chlorogenic acid (CA; 0, 0.5, 1, and 2%) with and without ultrasound (US) to inactivate P. fluorescens planktonic and biofilm cells were investigated. CA and US had great synergistic effects against P. fluorescen s planktonic and biofilm cells. CA combined with US seriously destroyed the integrity of cell membrane and cause the ATP and nucleic acid leakage. CA combined with US effectively decreased the polysaccharide contents in P. fluorescens biofilms. Abstract: This study investigated the synergistic efficacy of ultrasound (US, 50 kHz, 400 W) in combination with chlorogenic acid (CA; 0, 0.5, 1, and 2%) to inactivate Pseudomonas fluorescens planktonic and biofilm cells. The P. fluorescens planktonic and biofilm cells were treated with CA with and without US for 5, 10, 20, 30, or 60 min. Results showed that US enhanced the efficacy of CA for inactivation of both P. fluorescens planktonic and biofilm cells. Treatment with 2% CA and US could completely inactivate P. fluorescens planktonic cells within 10 min and the biofilm cells within 30 min. Confocal laser scanning microscopy (CLSM), scanning electron microscopy (SEM), ATP, and nucleic acid release assays indicated that the combination of US and CA could quickly damage the integrity of P. fluorescens planktonic and biofilm cell membranes. The combined treatment effectively inactivates P. fluorescens planktonic and biofilm cells via the synergetic destruction of the biofilm structure and bacterial cell integrity.